Characterization and bioactivities of carboxymethyl cellulase produced by alcaligenes faecalis using disposed x-ray film as the substrate - Noor Afifah, Fauzi (2019)
Cellulase is a beneficial enzyme that has been long used in production of animal feed, in the formulation of detergents, juice clarification, paper manufacturing and wine production. Nowadays, production of cellulases enzyme from the bioconversion of cellulosic waste has been extensively practiced. The enzymes typically can be acquired from microorganisms especially bacteria and fungi. Furthermore, potential capability of unknown microorganisms to digest cellulosic material can be exploited using a new substrate, which is x-ray film waste. X-ray film is a form of hazardous waste which contains silver residue, alongside cellulase which can be produced by any microorganisms that feed on cellulose found in x-ray film waste. The objectives of this project are (i) to isolate, screen and identify microorganisms from water, soil and food sources, thus select on most potent isolates, (ii) to optimize the effect of bacterial isolates using disposed x-ray film as the substrate on cellulase production, and (iii) to purify and characterize the bioactivity of cellulose. The samples of Panching Soil (PS1) and Chicken Liver (CL8A) were selected as the most potent isolates after screening from 27 initial isolates. After optimization of CMCase and avicelase productions, only CMCase was selected for further process as it preferred the x-ray film as substrate. The optimum condition that enhanced the CMCase production was investigated using “One Factor at a Time” (OFAT) method, involving 7 different factors; incubation condition, carbon source, nitrogen source, initial pH, amount of substrate, inoculum size and vitamin. PS1 achieved highest CMCase activity of 0.934 U/ml in shaking condition, with 0.4 % w/v starch, 0.1 % w/v malt extract, 2.5 g amount of substrate, 2 ml inoculum size and 2 % w/v thiamine with pH 8 of production media. Whereas, CL8A achieved highest CMCase activity of 4.559 U/ml in shaking condition, with 0.4 % w/v lactose, 1.5 g amount of substrate, pH 9 of production media and the rest of the factors were similar to PS1. However only CL8A was selected for partial purification of enzyme as it displayed higher enzyme productivity. CL8A was produced on a large scale to carry out ammonium sulphate precipitation after the optimization process. CMCase yield of 6.49 % was obtained and the molecular weight of the enzyme has been analysed using electrophoresis method resulting in 60 kDa. Microorganism of PS1 was identified as Gram negative bacteria Providencia rettgeri, while CL8A was identified as Gram negative bacteria Alcaligenes faecalis. The CMCase enzyme fraction was catalysed using 2 different factors and was found to be stable at 25 °C and pH 5. In conclusion, the isolates derived from food waste (A. faecalis) and soil (P. rettgeri) displayed a good potential as cellulolytic microorganisms and were able to degrade x-ray film and produce CMCase.